Optimale leerschema’s bij dementie - Diesfeldt, Han F.A. (Tijdschrift voor Gerontologie en Geriatrie, 2015)
Bespreking:Materne, C. J., Luszcz, M.A. & Bond, M.J. (2014). Onceweeklyspaced retrieval training is effective in supportingeveryday memory activities in community dwellingolder people with dementia. Clinical Gerontologist,37:475–492.Creighton, A.S., Davison, T.E., Van der Ploeg, E.S.,Camp, C. J. & O’Connor, D.W. (2015). Using spaced retrievaltraining to teach people with dementia to independentlyuse their walking aids: two case studies. ClinicalGerontologist, 38:170–178.